The Effect of Mixing Diesel Fuel with Cottonseed Oil and Coconut Oil on The Performance of 4-Stroke Diesel Engine - Iswantoro, Adhi; Fathallah, Aguk Zuhdi Muhammad; Semin,; Saputra, Ramdhan Febrianto (International Journal of Marine Engineering Innovation and Research, 2025)
Research on biodiesel as an alternative fuel has been widely carried out. Such as mixing one type of oil mixed with diesel fuel with a certain composition. In this research, biodiesel was made by mixing two types of oil and then mixed with diesel fuel with a composition of 30:80, where 30% for mixed oil that is cottonseed oil and coconut oil, then 80% for diesel fuel. And then in this research, the composition between cottonseed oil and coconut oil must be found, so that it will get the best composition between cottonseed oil and coconut oil. For comparison in performance between mixed biodiesel with 4 cSt and 6 cSt, and in the mixing process, using mathematical calculation methods, then the mixing results must meet SNI standards (Standard Nasional Indonesia / Indonesian National Standards). In this research, 4-stroke diesel engines with one cylinder were used. From the experiments and data analysis, biodiesel with 6 cSt more powerful, torsion and BMEP better than mixed biodiesel 4 cSt.